2017
DOI: 10.1080/08927022.2017.1402307
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of binary mixtures of hard colloidal cuboids

Abstract: We perform extensive Monte Carlo simulations to investigate the phase behaviour of colloidal suspensions of hard board-like particles (HBPs). While theories restricting particle orientation or ignoring higher ordered phases suggest the existence of a stable biaxial nematic phase, our recent simulation results on monodisperse systems indicate that this is not necessarily the case, even for particle shapes exactly in between prolate and oblate geometries, usually referred to as self-dual shape. Motivated by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
(67 reference statements)
2
25
0
Order By: Relevance
“…To explain the origin of these experimental results, the same authors formulated a mean-field theory to calculate the phase diagram of HBPs in the presence of a magnetic field. Despite the good qualitative agreement between theory and experiments, the former neglects the effect of size polydispersity, being crucial to stabilise the N B phase [8], and is limited by the strong approximations imposed by the Zwanzig model, which was shown to be not especially accurate to describe the phase behavior of HBPs [2,5].In this work, we perform Monte Carlo (MC) simulations of freely-rotating monodisperse HBPs in the presence of an external field that promotes a phase transition from the isotropic (I) or uniaxial nematic (N U ) phase to the N B phase. Because our main interest is gaining an insight into the energetics associated to this process, the field strength is a simulation parameter that assumes values between * f ≡ f β = 0.1 and 3, with β the inverse temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To explain the origin of these experimental results, the same authors formulated a mean-field theory to calculate the phase diagram of HBPs in the presence of a magnetic field. Despite the good qualitative agreement between theory and experiments, the former neglects the effect of size polydispersity, being crucial to stabilise the N B phase [8], and is limited by the strong approximations imposed by the Zwanzig model, which was shown to be not especially accurate to describe the phase behavior of HBPs [2,5].In this work, we perform Monte Carlo (MC) simulations of freely-rotating monodisperse HBPs in the presence of an external field that promotes a phase transition from the isotropic (I) or uniaxial nematic (N U ) phase to the N B phase. Because our main interest is gaining an insight into the energetics associated to this process, the field strength is a simulation parameter that assumes values between * f ≡ f β = 0.1 and 3, with β the inverse temperature.…”
mentioning
confidence: 99%
“…In the arXiv:1811.03677v1 [cond-mat.soft] 8 Nov 2018 following, we discuss the main aspects of the model and simulation methodology applied. The interested reader is referred to our previous works for additional details [2,5].…”
mentioning
confidence: 99%
“…The contributions to this issue reflect, first of all, the diversity of self-assembly applications described above. For example, Patti and Cuetos [1] explore the phase behaviour of colloidal suspensions of cuboidal particles with potential relevance for liquid crystal displays, whereas Rozhkov et al [2] present a detailed study of magnetic colloids that can be used to develop new responsive soft materials. The interactions between nanoparticles and surfactant micelles, and their effect on the rheology of suspensions, is the focus of the paper by Sambasivam et al [3].…”
Section: Engineering Self-assemblymentioning
confidence: 99%
“…Here, with one exception [9], all papers apply some form of coarse-graining in their simulations. It is common to represent colloids [1,2] and nanoparticles [3,4] as single interaction sites instead of describing them in atomistic detail, whereas surfactants [5,8] and biomolecules [7] are usually modelled as a collection of beads, thus preserving some of their structure and flexibility. Although this reduction of the number of interaction sites may sometimes appear quite drastic, it is often a direct consequence of the need to sample large time and length scales in order to probe the self-assembly mechanism.…”
Section: Engineering Self-assemblymentioning
confidence: 99%
“…6 The stability of this N B phase was ascribed to the particles' quasi self-dual shape, a geometry in between oblate and prolate, and to their significant size dispersity, which hinders the formation of the Sm phase. This key work has reignited recent interest, sparking numerous theoretical, experimental and computer simulation studies on hard board-like particles (HBPs) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and other biaxial geometries. 24,[28][29][30][31][32] Theoretical and computational studies on monodisperse systems have suggested that self-dual-shaped particles exhibit a higher tendency to form biaxial nematics.…”
mentioning
confidence: 99%